Gambaran Karakteristik ODHA Berdasarkan Lingkungan di Minangkabau Tahun 2018 - SRI HANDAYANI; ELIZA ARMAN; INGE ANGELICA (HANG TUAH MEDICAL JOURNAL, 2018)
Abstract Background Ranah Minang (West Sumatra Province) ranked 8 from 34 provinces in Indonesia with HIV/AIDS case rate of 18.8, above national case rate (17.2). Minang is a tribe that uphold Adat Basandi Syarak, Syarak Basandi Kitabullah custom or the custom of Minangkabau that based on Islam Sharia law. Islam religion in The Koran already stated haram (forbidden) of sexual activities or wrongdoings outside norm/ marriage such as: LBGTQ, drinking alcoholic beverages and using narcotics. These things are HIV transmission sources. This study aims to describe ODHA (Orang Dengan HIV/AIDS; HIV/AIDS patients) characteristics based on Ranah Minang location. Methods This study is an analytic observational study with cross-sectional design. This study was conducted in Ranah Minang (West Sumatera Province). Data are obtained by conducting questionnaire survey with quota sampling technique for a total of 28 ODHA (patients). Data were analyzed using univariate analysis with SPSS software. Results The result showed the role of peers’ influence in risky behaviors accounted for 96.4%, while the role of family accounted for 60.7% and the role of custom leader in the occurrence of HIV/AIDS incidence in cases accounted for 60.7%. Conclusion The number of risky behaviors prevalence in ODHA were found still quite high, based on the role of peers’ influence, as well as family and custom leaders’ influence. This study concluded that the environment still plays important role in the management of HIV/AIDS occurrences in Ranah Minang.